Editorial & Reviewer, Contents, Acknowledgements, Abstracts - Tjahjono, Endro Wahju (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
Journal of Industrial Research and Innovation Volume 16 No 1 April 2022 edition is still managed to publish. This volume presents various fields of transportation and material sciences. Transportation engineering nowadays is among the priority programs in Indonesia, which emphasize in Infrastructures development. Material sciences are therefore very relevant in supporting this theme. Thanks to continuoussubmission from contributors and hardwork of editor teams. Research and assessment were conducted by various institutions researchers in those fields. In this edition, the journal publishes important and interesting papers related to Materials engineering, such as : The Fatigue Life Assessment of Sideboard on Deck Barge Using Finite Element Methods,Corrosion of Brass Fishing Vessel Propeller in Artificial Seawater and Analysis of BLDC Electric Motor Shaft Treatment Model Using Numerical Method. The others paper published also about Transportation engineering : Measurement of Geometric Variations of a Railway Truss Bridge (Case Study: BH77 Railway Bridge) There are also paper are process technology : Study on Assessment and Feasibility of Hythane From POME to Improve Power Plant Performance and Optimization of Cross-linking Modification on Canna Starch with Sodium Acetate Using Response Surface Methodology. The editors always do their best to improve the quality of the Journal; especially now that we are heading towards an English language journal in order to increase the impact and citations. The next publication is scheduled with new appearance on Agustus 2022. As closing remarks, the editors always call for critics and suggestions to further improve this Journal.